Analysis of determining factors of fertility rate in Karangasem District - Wulandary, Ni Putu; Marhaeni, A.A.I.N. (Privietlab, 2024)
The purpose of this study is to analyze the simultaneous and partial influences of the ideal number of children, women's employment status, family perceptions of male children, age at first marriage, and women's education level on fertility rates in the Karangasem District, as well as to analyze the role of women's education level in moderating the impact of age at first marriage on fertility rates in the Karangasem District. This study employs a quantitative method with an associative approach. It utilizes Snowball Sampling and Accidental Sampling techniques for sampling. Data collection was conducted using observation, structured interviews, and in-depth interviews with a sample size of 99 Couples of Reproductive Age (CRA). The data analysis technique used is moderation regression analysis. The results of this study indicate: 1) The ideal number of children, women's employment status, family perceptions of male children, age at first marriage, and women's education level have a simultaneous and significant effect on fertility rates; 2) Age at first marriage and women's education level have a negative and significant impact on fertility rates; 3) The ideal number of children and family perceptions of male children have a positive and significant impact on fertility rates; 4) Women working in the formal sector have lower fertility rates than those in the informal sector; 5) Women's education level as a moderating variable strengthens the influence of age at first marriage on fertility rates.